Doughnut-shaped amniotic membrane transplantation in pediatric simple limbal epithelial transplantation after ocular chemical injury - Gustavo Ortiz-Morales; Reinaldo A. Moll-Auais; Julio C. Hernandez-Camarena; J. Homar Paez-Garza; Alejandro Rodriguez-Garcia (The Pan-American Journal of Ophthalmology)
Children of any age are at high risk for ocular chemical injuries and the development of limbal stem cell deficiency with severe visual consequences. Surgical options for ocular surface reconstruction at the pediatric age tend to have lower success rates than their adult counterparts. Herein, we report the results of a novel modification of the simple limbal stem cell epithelial transplantation using a doughnut-shaped amniotic membrane graft to avoid further visual axis obstruction during re-epithelization. Since younger children are a highly susceptible population suffering from chemical burns, with nearly half of them being at preschool (first months of life to 5 years) ages, such a technique may be more appropriate to reduce the time of visual obstruction and obtain faster visual rehabilitation.